'Communities are not at the periphery, rather they are at the centre of Restorative Justice in BC': an inquiry into the praxis of Restorative Justice in British Columbia, Canada. Issue 2 (3rd April 2021) - Asadullah, Muhammad; Morrison, Brenda
ABSTRACT: There has been ebbs and flows, since 1982, with the growth of Restorative Justice (RJ) practices in British Columbia (BC), Canada. To date there are more than seventy plus organizations that offers RJ practices in BC. Using in-depth key informant interviews, along with surveys, this research seeks to understand the genesis and praxis of RJ in BC. This study finds that the local community's involvement was of paramount importance to the growth of restorative justice. Key findings include the contribution of Community Justice Initiative Langley, Community Accountability Programs and SFU's Centre for Restorative Justice. A number of emergent themes are discussed in the paper that include the role of the written RJ script, and standardization. The findings are significant for a number of reasons, first of all, it reveals the role of community, government and university collaboration. Secondly, emergent themes discussed in this paper illustrate the tensions within RJ praxis in BC where learning and growth are creating new understanding and insight. A detailed analysis on standardization debate and scripted vs non-scripted model of RJ are also discussed. This paper concludes that future research needs to focus on the relationship between restorative justice and Indigenous justice in BC.